2019
DOI: 10.2217/nnm-2018-0446
|View full text |Cite
|
Sign up to set email alerts
|

Limits and Challenges in Using Transport Inhibitors to Characterize How nano-sized Drug Carriers Enter Cells

Abstract: Aim: In this work we illustrate limits and challenges associated with the use of pharmacological inhibitors to study how nanomedicines enter cells and show how such limits can be overcome. Materials & methods: We selected a panel of six common pharmacological inhibitors and a model nanoparticle–cell system. We tested eventual toxicity by measuring cell viability. We confirmed drug efficacy by measuring the uptake of control markers for the pathways involved by flow cytometry and fluorescence microscopy. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 70 publications
2
75
0
Order By: Relevance
“…We previously performed an extensive study on these aspects and carefully optimized their use on HeLa cells, in order to demonstrate their efficacy and minimize their toxicity. 49 The same conditions were applied for this study. There, we also found that the presence of serum can strongly limit the efficacy of some of these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…We previously performed an extensive study on these aspects and carefully optimized their use on HeLa cells, in order to demonstrate their efficacy and minimize their toxicity. 49 The same conditions were applied for this study. There, we also found that the presence of serum can strongly limit the efficacy of some of these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is well established that perturbation of a cellular mechanism might as well lead to the alteration of other mechanisms. Therefore, when performing such studies, it is important to have appropriate controls to verify the effect of the selected treatment on the pathway of interest and exclude potential artefacts of this kind [22,133,158].…”
Section: Methods To Characterize Uptake Mechanismsmentioning
confidence: 99%
“…Apart from RNAi, so far, many studies on the uptake of nanosized materials make use of transport inhibitors, whose action on cells is instead very fast. However, some of these inhibitors lack specificity, they might interfere with multiple pathways, and they can cause cellular toxicity [22,133,158,213]. In contrast to these approaches to block uptake pathways, other strategies can be found in which proteins are instead overexpressed, in order to eventually detect an increase in nanoparticle uptake [17].…”
Section: Methods To Characterize Uptake Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations